(untitled) (Research, Society and Development, 2021)
Introduction: The experience of man during the course of the pregnancy of his wife must go through the personal, established interaction with pregnancy, the companion and the family, for this connection to take place it is necessary that he be encouraged to participate since prenatal birth. Objective: to analyze nursing conducts in the face of men’s encouragement in prenatal care. Methodology: The survey in question is a bibliographic, descriptive and exploratory review, based on articles published in periodicals. The data collection took place in September 2021, the inclusion criteria were articles published in the Portuguese language, available in full free of charge, from January 2016 to September 2021, in the database of ScieELO and LILACS. Results: This study was based on 10 articles. This study has shown important results that in order for the partners to have a good membership in prenatal monitoring, it is essential that systematic planning of actions be carried out, and these should include reception, empathy, Effective communication and proactive actions of education in fundamental health to achieve the link between professionals of Basic Attention and users Final considerations: It is concluded that the nurse is the main professional who has the responsibility of initially welcoming the partner and granting that individual the opportunity to become more directly involved in the gravitational process, both in individual consultations and in group events, making room for the figure of the father to be the protagonist of a new situation.